Behavioral and Emotion Disorder in Childhood: A Review - Kale, Alpana; Salve, Priyanka (Innovational: Journal of Nursing and Healthcare, 2024)
Behavioral problems among school going children are of significant concern to teachers and parents. These are known to have both immediate and long-term unfavorable consequences. Mental health problems in children and adolescents include several types of emotional and behavioral disorders, including disruptive, depression, anxiety, and pervasive developmental (autism) disorders, characterized as either internalizing or externalizing problems. Disruptive behavioral problems such as temper tantrums, attention deficit hyperactivity disorder, oppositional, defiant, or conduct disorders are the most common behavioral problems in preschool and school age children. Childhood behavior and emotional problems with their related disorders have significant negative impacts on the individual, the family, and the society. They are commonly associated with poor academic, occupational, and psychosocial functioning. Despite the high prevalence, studies on psychiatric morbidity among school children are lacking in our country. Identification and management of mental health problems in primary care settings such as routine Paediatric clinic or Family Medicine/General Practitioner surgery are cost-effective because of their several desirable characteristics that make it acceptable to children and young people (e.g., no stigma, in local setting, and familiar providers). This review provides prevalence, etiology, neurobiology, complication, assessment, diagnosis, and management of behavioral and emotional disorders in children